Political Corruption: Rise of Social Aid Politicization by Government in Grassroots Campaign 2024 Elections - Daffa Ladro Kusworo,; Titi Anggraini, (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2024)
The cruciality of 2024 General Election is inseparable from complex shift in democratic landscape as a structural-economic direction of state life. Competition between pairs candidates through their respective electoral political strategies is main focus of the community, one of which is Social Assistance (Bansos) which is often target of electoral commodities at grassroots base. President through his track record is also indicated by politicization Social Assistance by going to several regions to provide indirect support during the 2024 Election, as well as several ministers who further strengthen the indication of political corruption. This research uses a normative method that refers to conceptualization of political corruption and Law 7 of 2017 concerning Elections. The results showed that the identification of political corruption during the election period begins by looking at the policy formulation process which is often manipulated and looking for gray areas, such as the Election Law limiting Bawaslu to only take action against Paslon participants or teams who have registered with the KPU, and the absence of restrictions on the provision of Social Assistance. The discovery of the track record of politicization of social assistance by the government should be suspected during the campaign period ahead of the 2024 Election vote and become an evaluative tool for the government, both from the distribution method to the prohibition in certain moments. We can no longer prevent practices that have occurred, so what is expected is an ideal improvement recommendation for future elections.